Designing a Quantum Leadership Model in Secondary Schools Based on Grounded Theory - Delgarm, Maria; Shafizadeh, Hamid; Soleimani, Nader (Iranian Journal of Educational Sociology, 2022)
Purpose: Considering the role of quantum leadership in improving the performance and effectiveness of organizations, the aim of the current research was to design a quantum leadership model in secondary schools based on grounded theory.Methodology: This was an applied qualitative study and its population included experts and principals of the educational system of Iran in 2020. A total of 20 people were selected using snowball sampling. The data collection tool included a semi-structured interview, the validity of which was confirmed by the review of participants and the review of non-participating experts, and its reliability was obtained 0.83 by calculating the inter-coder agreement. The data were analyzed by the coding method based on the grounded theory in MAXQDA software.Findings: The results showed that the quantum leadership model in secondary schools consisted of 45 concepts in 8 components and 6 categories. The category of causal conditions included two components of building quantum trust and agreement and quantum thought. The category of background conditions included one component of quantum development platform. The category of intervention conditions included one component of positive and negative interveners. The core category included a component of quantum school, the category of strategies included two components of quantum leadership and quantum creativity, and the category of outcomes included a component of quantum learning. Finally, the quantum leadership model in secondary schools was designed based on the grounded theory.Conclusion: According to the quantum leadership model in secondary schools and based on the experts and principals of the education system of Iran, it seems necessary to plan to improve the status of schools by improving the identified concepts and components